การจำลองกระบวนการดักจับก๊าซคาร์บอนไดออกไซด์ด้วยเอมีนศักยภาพสูง - วริศรา แก้วคำ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The purpose of this study is to developed CO2 capture process for a coal-fired power plant by using CO2 capture technology with an amine absorbent. Furthermore, this paper also focused on minimizing the energy used in the process and increase of CO2 removal efficiency. The amine absorber for CO2 absorption is ternary amines Monoethanolamine (MEA), Diethanolamine (DEA) and Methyl-diethanolamine (MDEA). The amine absorption process is simulated in the absorber and regenerator tower at the industry level by using Aspen HYSYS program. All simulated scenarios were calculated at 90% CO2 capture rate. The analysis of this studied showed that aqueous solution of 46.25%wt DEA was the case with the lowest total process cost of $1,105,589 per year. In the other hand, aqueous solution of 46.25%wt MDEA was the case with the highest total process cost of $115,387,127 per year.